Cr3C2 assisted ultrafast high-temperature sintering of TiC - Sun, Yu; Zhao, Liang; Guo, Rui-Fen; Shen, Ping (Journal of the European Ceramic Society, 2023)
The strong covalent bonding of TiC renders its densification through conventional sintering difficult. Here, we propose a method involving liquid-phase-assisted ultrafast high-temperature sintering (UHS) for obtaining nearly full density of TiC ceramics by the addition of Cr3C2. The samples were heated at a rate of 600 °C/min to 2200 °C and held at this temperature for 1 min. The effects of sintering parameters and the Cr3C2 content on the relative density and microstructure of the sintered samples were investigated. The main causes of rapid densification were particle rearrangement associated with the Cr3C2 liquid phase, dissolution-reprecipitation associated with the solid solution, and the weak evaporation of Cr formed during UHS. In particular, the addition of Cr3C2 helped increase the hardness and elastic modulus of TiC significantly. This paper presents an effective and extensible method involving UHS for rapidly obtaining dense ceramics.